1990
DOI: 10.1002/1097-0142(19901101)66:9<1904::aid-cncr2820660908>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of granulocyte colony-stimulating factor on neutropenia due to chemotherapy for non-Hodgkin's lymphoma

Abstract: The authors administered recombinant human granulocyte colony-stimulating factor (rhG-CSF) to 16 patients with advanced non-Hodgkin's lymphoma treated with combination chemotherapy. Groups of three to five patients were treated with 50, 100, 200, and 400 micrograms/m2 per day of rhG-CSF by intravenous infusion for 14 days, beginning 3 days after chemotherapy. There was a strong linear relationship between the dose and the area under the curve over this dose range. The rhG-CSF was rapidly cleared from serum, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The benefit of such treatment strategies remains controversial. However, most studies report a shorter duration of neutropenia with a lower incidence of infections in the hemopoietic growth factor–treated patients . It is believed that hematopoietic growth factors when administered concomitantly with chemotherapy this treatment induces a recycling of the leukemic cells and increases their chemosensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…The benefit of such treatment strategies remains controversial. However, most studies report a shorter duration of neutropenia with a lower incidence of infections in the hemopoietic growth factor–treated patients . It is believed that hematopoietic growth factors when administered concomitantly with chemotherapy this treatment induces a recycling of the leukemic cells and increases their chemosensitivity .…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Several studies have therefore shown beneficial therapeutic effects in applying recombinant G-CSF (rG-CSF) to patients with chemotherapyassociated leukopenia. 17,19,20 In addition, rG-CSF has been used, along with antibiotics, to treat pneumonia in animal models, 21 and it was found that leukopenic animals showed an increased survival under rG-CSF therapy. Other studies show a beneficial effect of rG-CSF, even in non-neutropenic animals.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence suggests a probable involvement of G-CSF in human early B-cell ontogeny. Some clinical studies showed that administration of G-CSF in lymphoproliferative disorders stimulated only granulopoiesis but not malignant lymphoid cells [23,24,25]. This clinical evidence suggests that G-CSF receptors expressed on lymphocytic leukemia cells are less functional than those on normal hematopoietic cells.…”
Section: Discussionmentioning
confidence: 99%